Геометрическая модель и граничные условия теплообмена ротора высокого давления турбоустановки Т-100/120-130 ПАО "Харьковская ТЭЦ-5" - Черноусенко, Ольга Юрьевна; Бутовский, Леонид Сергеевич; Пешко, Виталий Анатольевич; Мороз, Олег Сергеевич (НТУ "ХПИ", 2017)
Европейский союз принял директиву о развитии когенерации до уровня в 10 % от общей выработки электроэнергии. Основные экономические проблемы ТЭЦ проявляются при снижении тепловой нагрузки и соответствующем повышении себестоимости электроэнергии. С точки зрения экологической безопасности городов централизованное теплоснабжение является преимущественным видом поставки тепла. Построена геометрическая модель ротора высокого давления (РВД) с учетом данных визуального контроля, полученного при планово-предупредительном ремонте. Рассчитаны граничные условия (ГУ) РВД при пусках из холодного состояния (ХС), из неостывшего (НС) и из горячего состояния (ГС), которые изменяются во времени в течение всего периода пуска. При расчете ГУ РВД учтены изменения параметров на переменных режимах работы.

The experience of Denmark, Finland and Russia shows that up to 90% of the urban demand in heat and electricity can be provided in a joint cycleof their production. The European Union adopted a directive about the development of cogeneration to a level of 10% of total electricity generation. From the point of view of the energy business there is valuable in big cities the presence of the combined networks of consumers who use both electricity and heat. Cogeneration systems of most Ukrainian cities are characterized by a high degree of deterioration of thermal power station and thermal networks. The heat consumption of the population is also reduced because of high tariffs for thermal energy. Main economic problems CHP manifested during reducing of the heat load and the corresponding increase in the cost of electricity. In terms of environmental safety of urban district heating it is advantageous. Therefore, the extension of exploitation of the heat power stations is actual and requires special studies. The geometric model of the high pressure rotor, based on visual inspection dates during the repair works, is building. To optimize the calculations in the model there were selected the regulating stage and the first four non-regulated stages of the high pressure rotor, where the metal temperature is high and we have the maximum temperature gradients in the starting regimes. The boundary conditions during the starting from the cold, non-hot and hot states were calculated. When calculating the boundary conditionsthe changes of the working parameters are were taken into account.
The geometric model and boundary conditions of heat transfer of the high pressure rotors of the turbine T-100/120-130 of the PJSC "Kharkiv HPS-5"
Keywords: централизованное теплоснабжение; пуск; холодное состояние; ХС; РВД; ГУ; горячее состояние; неостывшее состояние; centralized heat power; cold state; hot state; non-hotstate